Investigation and Analysis of Radiation Dose and Typical Values in Adult Computed Tomography Examinations - Bin ZHANG; Jingbo DU; Boyang ZHANG; Shuo TONG; Xueyan KUI; Taoran FENG; Hailong YANG; Jianyong LIAO; Yongxian ZHANG (CT Lilun yu yingyong yanjiu)
Objective: This study aimed to investigate the radiation dose levels and typical values of computed tomography (CT) devices in our unit, providing a basis for optimizing radiation protection. Methods: The scanning parameters and radiation dose data of head, chest, and abdominal examinations from five CT devices in our hospital from July to December 2023 were retrospectively analyzed. Median values were determined and compared with domestic and international diagnostic reference levels (DRL). Results: The typical values for the volume CT dose index (CTDIvol) and dose length product (DLP) were 54.40 mGy and 735.80 mGy·cm, 14.20 mGy and 443.60 mGy·cm, and 16.40 mGy and 678.20 mGy·cm for head, chest, and abdomen, respsectively. The highest CTDIvol and DLP typical values were observed in head examinations, followed by abdominal and chest. CTDIvol and DLP for head examinations slightly increased with age. Significant statistical differences were found in CTDIvol and DLP for head and abdominal CT examinations with different years of use. Here, the DLP values were lower than those in other countries. Excluding a slightly higher head DLP, all other radiation doses were below the national health industry standards. Abdominal DLP was higher than other provinces and cities. Conclusion: Radiation doses of adult CT examinations in this survey are consistent with domestic and international results. Standardized training and optimization of the scanning range in CT examinations are needed to reduce unnecessary radiation exposure to patients.